Germany : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The staff report for the 2004 Article IV Consultation on Germany highlights economic developments and policies. Profitability in nonfinancial firms has picked up, and corporate balance sheets are being repaired. On the policy front, Germany has made important headway over the past year in addressing deep-seated structural problems. The financial sector is recovering, and updated stress tests confirm the system's resilience, but progress in market-driven restructuring has been slow. Notably, important strides have been made in pension and health care reform, and in reforming unemployment benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet